The effect of tranexamic acid on hidden bleeding in older intertrochanteric fracture patients treated with PFNA. Issue 3 (March 2018) - Tian, Shuwei; Shen, Zheyuan; Liu, Yang; Zhang, Yanlong; Peng, Aqin
Abstract: Objective: To investigate the effect of tranexamic acid (TXA) on hidden bleeding in older intertrochanteric fracture patients treated with intramedullary nails. Method: Between January 2016 and January 2017, 100 cases of intertrochanteric fractures eligible for the study were treated with proximal femoral nail antirotation (PFNA) in our hospital. All patients were divided into two groups of 50 patients each: the TXA group and a blank control group. In the TXA group, all patients received TXA at a dose of 10 mg/kg −1 intravenously, 10 min preoperatively and 5 h postoperatively. The control group did not receive TXA. We recorded the volume of intraoperative blood loss and postoperative drainage, and the need for postoperative blood transfusion and transfusion volume for all patients. Blood routine examination was performed on the day of surgery and 2 days postoperatively. We calculated the total blood loss and hidden blood loss in the two groups separately according to the Gross equation. All patients underwent deep vein ultrasound of the lower limbs preoperatively and 1 week postoperatively to detect thrombosis. Results: Compared with controls, patients in the TXA group had lower: overt bleeding (50.59 ml; p = .012), total blood loss (181.58 ml; p = .005), hidden blood loss (130.64 ml; p = .037), volume of blood transfusion (110.0 ml; p = .019), and 20% lower transfusion rate compared with the control group. Patients receiving short-nail fixation had significantly lower hidden blood loss compared with patients receiving long-nail fixation (p < .05). However, we found no statistically significant difference in the incidence of deep vein thrombosis in the lower limbs between the two groups (p = .938). Conclusion: TXA significantly reduced hidden blood loss in older intertrochanteric fracture patients treated with intramedullary nails without an increased risk of thrombosis in lower limb deep veins.